Non-Deep Physiological Dormancy in Seed and Germination Requirements of Lysimachia coreana Nakai - Saeng Geul Baek (MDPI AG, 2021)
This study aimed to determine the type of seed dormancy and to identify a suitable method of dormancy-breaking for an efficient seed viability test of Lysimachia coreana Nakai. To confirm the effect of gibberellic acid (GA3) on seed germination at different temperatures, germination tests were conducted at 5, 15, 20, 25, 20/10, and 25/15 °C (12/12 h, light/dark), using 1% agar with 100, 250, and 500 mg·L−1 GA3. Seeds were also stratified at 5 and 25/15 °C for 6 and 9 weeks, respectively, and then germinated at the same temperature. Seeds treated with GA3 demonstrated an increased germination rate (GR) at all temperatures except 5 °C. The highest GR was 82.0% at 25/15 °C and 250 mg·L−1 GA3 (4.8 times higher than the control (14.0%)). Additionally, GR increased after cold stratification, whereas seeds did not germinate after warm stratification at all temperatures. After cold stratification, the highest GR was 56.0% at 25/15 °C, which was lower than the GR observed after GA3 treatment. We hypothesized that L. coreana seeds have a non-deep physiological dormancy and concluded that 250 mg·L−1 GA3 treatment is more effective than cold stratification (9 weeks) for L. coreana seed-dormancy-breaking.